2014
DOI: 10.1182/blood-2013-10-529628
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies identifies ORM1 as a novel gene controlling thrombin generation potential

Abstract: Key Points• Genetic variations at the ORM1 locus and concentrations of the encoded protein associate with thrombin generation.• These findings may guide the development of novel antithrombotic treatments.Thrombin, the major enzyme of the hemostatic system, is involved in biological processes associated with several human diseases. The capacity of a given individual to generate thrombin, called the thrombin generation potential (TGP), can be robustly measured in plasma and was shown to associate with thrombotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
(60 reference statements)
3
27
0
Order By: Relevance
“…In agreement with a previous study [ 37 ] we observed a high significant association between thrombin generation and prothrombin G20210A mutation. This genetic variation is a well-known genetic risk factor for VTE [ 1 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a previous study [ 37 ] we observed a high significant association between thrombin generation and prothrombin G20210A mutation. This genetic variation is a well-known genetic risk factor for VTE [ 1 ].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, thrombin generation phenotypes have been associated significantly with genetic variants in haemostatic genes such as F5 , F2 , FGA , F10 , F12 and TFPI [ 7 , 36 ]. It has been reported recently that there is a new association between thrombin generation variability and the ORM1 locus [ 37 ]. It is important to note that known genetic risk factors have been estimated to account for <30% of VTE cases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe heterogeneity in the effects of the two SNPs according to sex nor to F5 rs6025 or F2 rs1799963 mutations (Tables S3 and S4). Although the six known VTE-associated loci affect VT risk through a modulation of known hemostatic traits (i.e., levels of von Willebrand factor and Factor VIII for ABO, of FXI for F11, of endogenous thrombin potential for F2, of resistance to activated protein C for F5, of fibrinogen for FGG, and of protein C for PROCR [26][27][28][29][30][31][32][33] ), the loci of the two discovered genetic associations were not in or near genes that are currently known to influence hemostasis. We then explored whether these SNPs were associated with well-characterized hemostasis phenotypes that are associated with thrombotic propensity.…”
Section: Resultsmentioning
confidence: 99%
“…The rare A allele is associated with elevated plasma prothrombin (FII) levels induced by a more efficient translational machinery of the mRNA harbouring the A allele (Gehring et al , ). It is also associated with thrombin generation, as is the intronic F2 rs3136516 G/A, in complete negative LD with the rs1799963 (Rocanin‐Arjo et al , ). In the INVENT study, the rs3136516 A allele, with frequency ~0·40, demonstrated strong statistical evidence ( P = 5·65 10 −6 ) for association with VTE, after adjusting for the effect of the rs1799963 polymorphism.…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%